Community Structure of Terrestrial Invertebrates Inhabiting a Tidal Marsh Islet in the Mediterranean Sea (Gulf of Gabes, Tunisia). (2002) - Colombini, I.; Chelazzi, L.; Fallaci, M.
Abstract : The composition of the terrestrial arthropod community of a tidal marsh islet in the Gulf of Gabes (Tunisia) was studied during two seasons (spring, autumn). The study was conducted on a small islet located in an area where the highest tidal excursions of the Mediterranean occur. Standard trapping methods (pitfall traps, mobile cages) were used to evaluate specie richness and abundance in different areas of the islet. Diversity indices were calculated for coleopterans and isopods alone. The structure of the arthropod community varied a great deal from one season to the other and differences were found when seaward areas were compared with landward ones. El Bessila presented a particularly rich beetle community whereas only few isopod species occurred. The moderately high diversity levels found for the beetle indicate the influence of the high tidal excursions in modelling the structure of the community.